(untitled) (Research, Society and Development, 2021)
Temporomandibular disorders are characterized either by the presence of pain, swelling and disjunction of the temporomandibular joint or musculature. Thus, the use of the laser has great efficiency to anesthesia on this area, reducing inflammation and discomfort. The objective of this survey was to carry out an integrative review of the literature on the use of laser in the treatment of TMD, highlighting benefits, limitations, effectiveness, relevance and impact for oral health. The guiding question is: how effective is the use of low-level laser in the treatment of TMD? An integrative literature review had been done by searching scientific articles in the electronic databases Web of Science, PubMed and Medline, using the descriptors low-level laser therapy (LLLT), temporomandibular joint dysfunction (TMD) and orofacial, indexed in the period from 2015 to 2020 that dealt with case reports, clinical trial, review, meta-analysis and randomized controlled. There were excluded books and documents, and editorial articles, through the application of the words “and” and “more”. After the eligibility criteria, 7 articles published in English were analyzed. Studies have shown that the use of laser helps in the treatment of TMD regarding the patient comfort, reducing the healing period of the injury, pain and inflammation due to its analgesic and anti-inflammatory capacity. Its effectiveness is due to the increase of collagen content in the wound, stimulating the angiogenesis and the proportion of cells available for healing. Nevertheless, it is required that studies continue to be carried out, so that, matters like these are spread around to population, since this technique is promising for the area.